Nitrogen nutrition of young triticale plants grown under aluminium stress - Domingues,Ana Maria (2010)
Triticale has proven to be a tolerant crop in many places around the globe, under extreme climatic and edaphic conditions, particularly in Al-toxic soils. To suffice the growing food demand of the world population, one of the most important goal is the sustainable increase of cereal production avoiding the anthropogenic pollution, often air and groundwater contamination by volatilization and leaching of N compounds. The effects of enhanced ammonia proportion in relation to nitrate nutrition in hydroponics, with or without Al, were investigated on the short-term growth of triticale plants. Three days old plants of the Al-tolerant genotype TTE 9203 were submitted to 0 or 370 mM Al and received different NO3-/ NH4+ ratios with the four proportions 15:1, 8:1, 3:1 and 1:1 (with fixed total N concentration at 3.2 mM in all treatments). In relation to the corresponding control solutions, 370 mM Al induced important decreases in root length, ranging from 75.3 % to 47.3 %, reductions in fresh weight from 80 % to 60 % in roots, and from 89 % to 71 % in shoots, depending on the NO3-/ NH4+ ratio. A decrease in NO3- net uptake was shown by plants in the presence of Al. The most detrimental Al effect for young plant growth in nutrient solutions was observed with the 15:1 NO3-/ NH4+ ratio, which induced the highest reductions of length of the main root (52.7 % reduction relative to control) and of root biomass fresh weight (40.6 %) in four days of treatment. By the contrary, the plants grown in the 8:1 ratio solution with Al suffered the smallest reductions of root length (24.7 % in 370 mM Al treatment relative to control) and of root biomass fresh weight (20.3 %). Taken together the results indicate that NH4+ can alleviate Al toxicity in triticale and point out the ideal NO3-/ NH4+ proportion of 8:1 as the best for these young plants growth and N use efficiency, under acidic and Al toxic condition. Some economical and ecological advantages of NH4+- N sources use in plant fertilization are discussed.